2022
DOI: 10.3389/feduc.2022.1036668
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and job satisfaction: The mediating role of trust and leader-member exchange

Abstract: ObjectiveThe study aimed to examine the role of trust mediation and leader-member exchange in the influence of servant leadership on job satisfaction.BackgroundResearch on the relationship between servant leadership and academic job satisfaction is rare. The study of servant leadership in Christian higher education is dominated by non-research (conceptual), literature review, and church ministry, instrument development, verification, and validation, quantitative (pre- and post-test), quantitative (descriptive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 134 publications
1
11
0
1
Order By: Relevance
“…Table 1 shows the 14 research publications that were included in the scoping review based on the criteria stated above [12], [20], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]. The outcomes of the analysis revealed that the impact of servant leadership on leaders in educational institutions is more beneficial when successfully implemented, which could address the research questions.…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows the 14 research publications that were included in the scoping review based on the criteria stated above [12], [20], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]. The outcomes of the analysis revealed that the impact of servant leadership on leaders in educational institutions is more beneficial when successfully implemented, which could address the research questions.…”
Section: Main Findingsmentioning
confidence: 99%
“…In addition, two research investigations on servant leadership have been done in South Africa [20], [48], India [41], [42], and Turkey [38], [40]. The majority of the research investigations were conducted in Indonesia [44], [45], [46], [47]. In addition, four articles were published in 2021 [40], [41], [42], [48], followed by five pieces in 2022 [20], [38], [39], [46], [47].…”
Section: Background Of the Research Included In The Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the study by Visone (2022) was focused on teacher-to-teacher peer-evaluation-not department leader evaluation of teachers-this can be considered a close parallel or overlap with how department leaders' evaluations of teachers can be perceived if the department leader fosters a collegial peer to peer culture rather than a strictly hierarchical one. By fostering a "collegial visit" approach (Visone, 2022), department leaders might emphasize themselves as a type of "servant leader" to their department colleagues (Crippen & Willows, 2019;Dami et al, 2022). This perspective is especially relevant to department chairs in the K-12 school context, because in many cases, according to Mayers and Zepeda (2002), the department chair has the same or similar course load as their colleagues in the department.…”
Section: Evaluative Authoritymentioning
confidence: 99%